Effect of MOS, Baker Yeast, or Noni Leaves Extracts on Antibody Titers to NDV and AI Vaccine of Broilers Fed Corn-mungbean Base Diets - Murwani , Retno (International Journal of Poultry Science, 2010)
A research was carried out to study the effect of MOS, baker yeast, or Noni leave extracts on broilers antibody titers to NDV and AI vaccine. Broilers were fed corn-mungbean base basal diet. Two hundreds 204 Lohman MB-202 day old chicks were randomly assigned into four treatment diets i.e. 1) commercial diet (Dc), 2) basal diet with addition of MOS (DMOS), (3) basal diet with inactivated baker yeast (DYEAST), (4) basal diet with inactivated baker yeast and Noni leaves extracts (DY+L). Basal diet, commercial diet and water were given ad libitum. NDV and AI vaccine were given simultaneously via subcutaneous on day 4. Serum antibody titers were measured on day 18, 21, 25 and 30 by Haemaglutination Inhibition Test and expressed as Geometric Mean Titer (log2). Antibody titers to NDV and AI vaccine were already detectable two weeks after vaccination (on day 18). There were no significant difference of antibody titers to both vaccines among all groups. These results showed that either MOS, or yeast, or combined yeast and noni leaves extracts can be used in corn-mungbean base diet to support broilers production against NDV and AI routine vaccination.